Diastasis recti abdominis. Surgical or a physiotherapist problem? - Polski, Paweł; Polska, Paulina; Tobiasz, Michał; Turkosz, Agnieszka (Journal of Education, Health and Sport, 2019)
The aim of this work is to show the problem of the diastasis of abdominal muscles most often found in pregnant women, postpartum and obese people. After delivery, simple muscles do not always return to their normal position. They remain significantly weakened and their function disturbed. It can lead to postural disorders and chronic back pain. To detect the possible risk of simple muscle divergence, routine tests are used. When determining the distance, it is recommended to increase physical activity and to implement appropriate exercises in physiotherapy. The article contains practical tips on modifying abdominal muscle exercises and a description of the therapeutic exercises recommended in the event of abdominal muscle divergence.